Effects of treadmill exercise on hippocampal neurogenesis in an MPTP /probenecid-induced Parkinson’s disease mouse model - Sung, Yun-Hee (J Phys Ther Sci, 2015)
[Purpose] This study aimed to investigate the effect of treadmill exercise on non-motor function, specifically long-term memory, in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid-induced Parkinson’s disease mouse model. [Methods] A mouse model of Parkinson’s disease was developed by injecting 20 mg/kg of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine and 250 mg/kg of probenecid (P). We divided in into four groups: probenecid group, probenecid-exercise group, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid group, and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid-exercise group. Mice in the exercise groups ran on treadmill for 30 min/day, five times per week for 4 weeks. [Results] Latency in the passive avoidance test increased in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid-exercise group compared with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid group. In addition, the number of 5-bromo-2-deoxyuridine/NeuN-positive cells and 5-bromo-2-deoxyuridine/doublecortin-positive cells in the hippocampal dentate gyrus was higher in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid-exercise group than that in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid group. These changes were associated with the expression of brain-derived neurotrophic factor in the hippocampus. [Conclusion] Our results suggest that treadmill exercise may improve long-term memory in Parkinson’s disease mice by facilitating neurogenesis via increased expression of neurotrophic factors.